Age-related nest-site segregation in a solitary nesting population of white stork Ciconia Ciconia - Joanna T. Bialas; Irene Gaona-Gordillo; Łukasz Dylewski; Marcin Tobolka (Frontiers in Zoology)
Abstract Background Habitat selection plays a crucial role in avian reproductive success, with nest-site characteristics and individual traits influencing breeding outcomes. This study investigates the relationship between breeder’s age and nest-site selection in a population of white storks Ciconia ciconia, a long-lived, site-faithful species nesting solitarily in Western Poland. Using data collected from 2006 to 2024 on ring recoveries, nest dimensions, productivity, and habitat characteristics, we analyzed the age at which birds were first recorded on specific nests. Results Results revealed that older individuals were more likely to occupy larger nests and nests with higher productivity in previous years, suggesting the use of public information and a preference for high-quality sites. Interestingly, nest surface area, rather than height, was correlated with breeder’s age, while land cover surrounding the nest had a sex-specific effect. Older individuals also appeared to prefer nests with higher occupancy rates. Older females avoided human-altered habitats, whereas no such relationship was observed for males. Contrary to expectations, age-related differences were not associated with preferred foraging habitats like meadows and pastures. Conclusions These findings highlight that age-based segregation in nest-site selection reflects experience and competition, with older birds optimizing breeding success by leveraging key environmental and social cues. The results suggest that younger individuals may occupy suboptimal habitats, possibly due to competition or inexperience. Future studies should explore the role of site fidelity, age-assortative mating, and anthropogenic influences, such as supplementary feeding, to fully understand the dynamics of nest-site selection in white storks.